コオリ クッサク ギジュツ ノ テンボウ - 鈴木, 義男; スズキ, ヨシオ; Suzuki, Yosio (1985)
P(論文) 地盤掘削では, 孔内に泥水を循環させて切粉処理する方式が主流である。泥水循環は, 孔壁保守と切削具の冷却を目的とするが, これらは氷掘削では不要である。それで, 氷掘削では, 装置が大規模な泥水の孔内循環に代わり, 切粉を孔底のドリル内で処理するケーブルつり下げ方式のコアドリルが主流となった。この場合の掘削所要時間をきめる諸要素について, 現在の標準値を紹介する。さらに, 深いボーリングで問題となる孔径収縮対策の液封について説明した後, 他方式を含め, これまで実用化された氷掘削機の具体的説明と評価を行う。最後に, トンネルおよびトレンチの掘削について, グリーンランドでの実行例を紹介する。 In earth boring it is common to circulate drilling mud in the bored hole. The two purposes of the circulation, besides removal of cuttings, are to cool cutters and to preserve the hole, which are both unimportant in ice boring. Hence, because of its light weight, a cable-suspended core drill which treats cuttings locally is preferred to a drill using the mud circulation which needs heavy equipments. The drilling time with a core drill is discussed in detail. An important problem in deep ice boring is the hole closure due to ice pressure. Technique to fill the hole with liquid to cope with the hole closure is introduced. Then, various kinds of ice drills are introduced and assessed. Included are : auger drills, rotary machines, turbo drills, dyna drills, cable-suspended electromechanical and electrothermal drills, steam drills, hot-water drills and flame-jet drills. Tunnel and trench excavations carried out in Greenland are briefly introduced at the end. departmental bulletin paper